Financial crises and the asymmetric relation between returns on banks, risk factors, and other industry portfolio returns - Högholm, Kenneth; Knif, Johan; Koutmos, Gregory; Pynnönen, Seppo (Wiley, 2021)
We show that the relations between the returns on the banking industry, risk factors, and other industries often are asymmetric. Lagged banking industry returns seem to improve predictability but the positive impact of a 1-month lag of the return on the banking portfolio is much higher in the lower part of the return distribution. However, after the Dodd-Frank Act in 2010, the cross-autocorrelation with banks is changed and becomes negative in the upper part of the distribution. Returns on banks also seem to lead returns on five risk factors. This relation, however, is not robust across the distribution.
Keywords: banking industry; Dodd-Frank Act; financial crises; fi=Matematiikka|en=Mathematics|